Parameterizing Mesoscale Eddy Buoyancy Transport Over Sloping Topography - Aleksi Nummelin; Pål Erik Isachsen (Journal of Advances in Modeling Earth Systems, 2024)
Abstract Most of the ocean's kinetic energy is contained within the mesoscale eddy field. Models that do not resolve these eddies tend to parameterize their impacts such that the parameterized transport of buoyancy and tracers reduces the large‐scale available potential energy and spreads tracers. However, the parameterizations used in the ocean components of current generation Earth System Models rely on an assumption of a flat ocean floor even though observations and high‐resolution modeling show that eddy transport is sensitive to the potential vorticity gradients associated with a sloping seafloor. We show that buoyancy transport coefficient diagnosed from idealized eddy‐resolving simulations is indeed reduced over both prograde and retrograde bottom slopes (topographic wave propagation along or against the mean flow, respectively) and that the reduction can be skilfully captured by a mixing length parameterization by introducing the topographic Rhines scale as a length scale. This modified “GM” parameterization enhances the strength of thermal wind currents over the slopes in coarse‐resolution, non‐eddying, simulations. We find that in realistic global coarse‐resolution simulations the impact of topography is most pronounced at high latitudes, enhancing the mean flow strength and reducing temperature and salinity biases. Reducing the buoyancy transport coefficient further with a mean‐flow dependent eddy efficiency factor, has notable effects also at lower latitudes and leads to reduction of global mean biases.